Experimental and Theoretical Study of Ldpe: Evaluation of Different Food Simulants and Temperatures - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M; Torres-Mediano, A (2011)
Sin Editorial Disponible